PEMANFAATAN MEDIA INTERNET DAN FAKTOR PENDUKUNG MEDIA INTERNET DALAM KOMUNIKASI VIRTUAL PADA MASA PANDEMI COVID-19 DI KEMBANGAN UTARA - JAKARTA BARAT - Amzad Samudro; Islahuben Islahuben; Diah Fistiani Sukardiman (Universitas Mercu Buana, 2022)
The program for utilizing internet media and supporting factors for internet media in virtual communication during the Covid-19 pandemic in northern development is a program that aims to improve the quality of society in today's technology. This also fulfills the views and environment for people in northern kembangan. Utilization methods and internet media supporting factors in virtual communication during the Covid-19 pandemic are applied to keep activities like costs in cyberspace. The implementation of user activities and internet media supporting factors in virtual communication during the Covid-19 pandemic in northern development by the PPM report compilation team which was carried out virtually by the north kembangan community. The type of plan, from the target achievement and outcome, is to realize community values which include aspects of the benefits of the internet, supporting factors for virtual communication during the Covid-19 pandemic.